Internet service monitoring with mobile agents. - Gunter, M.
The Internet Engineering Task Force standardizes new IP technologies such as Differentiated Services and IP security that allow Internet service providers to offer new and enhanced network-level services. There is a need for a measurement infrastructure to monitor services, especially for support of end-to-end services across the Internet. The infrastructure should provide a safe way for customers to monitor the enhanced properties of the services they use. Also, providers should be able to use the infrastructure to ensure provider collaboration. We implemented a mobile-agent-based monitoring infrastructure for new and enhanced IP services
Keywords: DiffServ; Differentiated Services; IP security; IP technologies; ISP; Internet Engineering Task Force; Internet service monitoring; Internet service providers; QoS guarantees; Measurement infrastructure; Mobile agents; Monitoring infrastructure; Network infrastructure; Network-level services; Provider collaboration; Quality of service; Virtual private networks